(untitled) - Merki, Mary Bronson (New York, N.Y., 2003)
The book covers all aspects of teenagers health including understanding youth health, keep the body healthy, protecting health and safety anf the environment
Keywords: Sức khỏe học đường (trung học),Health education (Middle school),Teenagers,Thanh thiếu niên; Health and hygiene,Study and teaching (Middle),Vệ sinh và sức khỏe,Dạy và học (trung học)